Evolution And Analysis With An Accessibility Approach Of The Public Bus Transportation System Network In The City Of San Juan De Pasto Using Graph Theory - Argoty, Jorge Luis; Molina, Ciro. Jaramillo (Migration Letters, 2023)
The evolution of the public bus transportation road network in the city of San Juan de Pasto, capital of the department of Nariño in Colombia, is analyzed. The structures of the road networks of the bus system are analyzed at different moments in the history of the city of Pasto. Four time scenarios are studied, ranging from the date of creation in 1948 to the present year 2021, and their topological relationships and operating conditions in terms of accessibility are evaluated by means of graph theory. The analysis periods considered for the bus transportation system network are the years 1948, 1965, 2006 and 2021. Each of the networks is evaluated by means of status and network shape indicators to later analyze each indicator individually and between variables, by means of a correlation matrix, obtaining the evolution of the network development, the level of connection, the degree of cohesion, density and coverage of the San Juan de Pasto public bus transportation system network, from its creation to the present.